2011
DOI: 10.1007/s10354-011-0883-9
|View full text |Cite
|
Sign up to set email alerts
|

Hochfrequente elektromagnetische Wellen und unspezifische Gesundheitsbeschwerden: eine Literaturübersicht

Abstract: This is an update of a previous systematic review on the association between radiofrequency electromagnetic field (RF-EMF) exposure and health-related quality of life that included studies published before August 2007 [1]. Since then, nine randomized trials addressed short-term exposures from close-to-body RF-EMF sources such as mobile phones, and two observational studies investigated the effects of mobile phone use on health-related quality of life. Six randomized trials addressed short-term far-field exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…It was also observed that methodological quality was an important component for the strength of the associations, since studies with a higher risk of bias, mainly regarding exposure assessment and sample selection, reported more significant associations. More recent studies which tend to employ advanced exposure characterization methods did not suggest a significant effect; this is in agreement with the findings of Röösli and Hug (2011). Studies on perceived exposure showed generally stronger symptomatic effects and more consistent patterns, indicating an association with concentration problems and headache, while most of them yielded nonsignificant or contradictory results for sleep problems, dizziness, fatigue-related symptoms and tinnitus.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It was also observed that methodological quality was an important component for the strength of the associations, since studies with a higher risk of bias, mainly regarding exposure assessment and sample selection, reported more significant associations. More recent studies which tend to employ advanced exposure characterization methods did not suggest a significant effect; this is in agreement with the findings of Röösli and Hug (2011). Studies on perceived exposure showed generally stronger symptomatic effects and more consistent patterns, indicating an association with concentration problems and headache, while most of them yielded nonsignificant or contradictory results for sleep problems, dizziness, fatigue-related symptoms and tinnitus.…”
Section: Discussionsupporting
confidence: 83%
“…The estimated prevalence of these nonspecific physical symptoms (NSPS) ranges between 3.5% and 10% (Blettner et al, 2009;Schreier et al, 2006;Schrottner and Leitgeb, 2008). Although evidence that could support a causal association between exposure and outcome seems to be insufficient and inconsistent (Röösli and Hug, 2011;Röösli et al, 2010;Rubin et al, 2009), a possible effect of higher exposure levels cannot be ruled out yet because of methodological obstacles, primarily regarding bias related to exposure assessment and study design (Röösli, 2008;Röösli et al, 2010). Systematic reviews focusing mainly on experimental evidence suggest rather a nocebo effect which could imply an underlying psychological mechanism that leads to physiological responses and subsequent symptoms (Rubin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies that evaluated acute reactions of the human body to exposure to the radiofrequency-electromagnetic field (RF-EMF) also reported that no significant correlations were found between RF-EMF and headache or other symptoms [9-11]. In contrast to experimental study results evaluating the effects of short-term RF-EMF exposure, observational studies evaluating the health effects of low-level and long-term exposure to RF-EMF have tended to report a significant correlation between the use of mobile phones and adverse health effects [5,6,12].…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to determine if a causal relationship between exposure to EMFs and claimed health symptoms does exist and to identify biologically plausible mechanisms underlying this syndrome (for review, see [2, 6, 7]). Despite the growing wealth of evidences gathered both in vitro and in vivo on animal models, data from human case-control and double-blind trials attempting to correlate EMFs exposure and claimed symptoms, resulted so far controversial [810].…”
Section: Introductionmentioning
confidence: 99%